Dietary ω-3 Polyunsaturated Fatty Acid DHA: A Potential Adjuvant in the Treatment of Cancer. (23rd May 2013) - Merendino, Nicolò; Costantini, Lara; Manzi, Laura; Molinari, Romina; D'Eliseo, Donatella; Velotti, Francesca
Abstract : ω -3 Polyunsaturated fatty acids (PUFAs), mainly present in fish oil, are part of the human diet. Among PUFAs, docosahexaenoic acid (DHA) has received particular attention for its anti-inflammatory, antiproliferative, proapoptotic, antiangiogenetic, anti-invasion, and antimetastatic properties. These data suggest that DHA can exert antitumor activity potentially representing an effective adjuvant in cancer chemotherapy. This review is focused on current knowledge supporting the potential use of DHA for the enhancement of the efficacy of anticancer treatments in relation to its ability to enhance the uptake of anticancer drugs, regulate the oxidative status of tumor cells, and inhibit tumor cell invasion and metastasis.